Development of Character Education Through Positive Discipline of Madrasah Students - Aishya Shaharani; Waode Zahra Februannisa (Institut Agama Islam Negeri Sorong, 2023)
Character education is essential in the learning process to form positive attitudes and values in students. Discipline is one of the strengthening of character education that needs to be considered. The formation of the disciplinary character of students can use positive discipline methods. This article aims to explain and analyze the implementation of positive discipline to support student character education in MI Al-Ishlah Sorong City. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The data collected is then analyzed using analytical techniques designed by Huberman & Miles: data collection, reduction, data presentation, and conclusion. Teachers adopt a positive reinforcement and reward approach to increase student participation, cooperation, and responsibility. In addition, clear rules and fair consequences are also applied to develop good behavior and respect for the environment. In the context of character education, positive discipline helps students internalize moral values such as honesty, responsibility, and mutual respect. Students also learn to recognize and manage emotions positively and develop social skills that are important in everyday life. The results showed that positive discipline can be effective as a means of character education for students in MI Al-Ishlah Sorong City. Positive discipline can help students to understand positive values such as responsibility, cooperation, and honesty. In addition, the application of positive discipline can also help students to develop good social and emotional skills. Therefore, positive discipline can be used as one of the effective character education strategies for students at MI Al-Ishlah Sorong City.